Rediscovery of Gastrotheca chrysosticta Laurent, 1976 (Anura: Hemiphractidae) in Baritú National Park, Salta, Argentina - Akmentins, Mauricio Sebastián (2018)
We report the rediscovery of the Marsupial Frog Gastrotheca chrysosticta, 25 years after the last record of this species in Baritú National Park, Salta Province, Argentina.